Investigation of bacteremia after orthodontic banding and debanding following chlorhexidine mouth wash application - (:unkn) unknown (ANGLE ORTHODONTISTS RES EDUC FOUNDATION INC, 2001)
This study investigates the prevalence of bacteremia after orthodontic banding and debanding, following the application of a 0.2% chlorhexidine gluconate mouthwash. The banding and debanding groups were each composed of 40 young adult patients. In the banding group, patients were asked to rinse their mouth with chlorhexidine gluconate for 60 seconds just prior to fitting of the bands. In the debanding group, they were asked to use the mouthwash immediately before removal of bands and brackets. In both groups pre- and post-treatment blood samples were obtained with a strict aseptic technique. In the banding group, no bacteremia was detected in the pretreatment sample and 2.5% post-treatment bacteremia was detected in the post-treatment sample. In the debanding group, 2.5% bacteremia was found in both the pre- and post-treatment samples. The prevalence of post-treatment bacteremia found in the present study were compared with the findings of 2 preliminary studies in which the prevalence of bacteremia had been investigated after banding and debanding without a prior application of chlorhexidine mouthwash. The application of chlorhexidine mouthwash resulted in a decrease in the prevalence of bacteremia after banding and debanding, but the decrease was not statistically significant.
Keywords: bacteremia; orthodontic banding; orthodontic debanding; chlorhexidine gluconate; INFECTIVE ENDOCARDITIS; ANTIBIOTIC-PROPHYLAXIS; PREVENTION; MOUTHRINSES; GINGIVITIS; EXTRACTION; CHILDREN; EFFICACY; PATIENT; RISK